Korelasi Motivasi Menghafal dengan Hasil Hafalan Al-Qur’an Anak Usia Dini - Fitri Wah Yuni; Suci Midsyahri Azizah; Asna Nur Fadhillatul Ilmi (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2022)
The purpose of this research is to find out the correlation between the motivation to memorize the Qur'an and the results of early childhood memorization at RA Darul Fikri Bringinan Ponorogo. This research is in the form of quantitative data collection procedures through check lists, tests and documentation. The research population was 36 students in group B whose total sample was taken as a whole. This research design uses a correlation design which analyzes the relationship between two variables whose data is categorical, then the data analysis technique used is the Contingency Correlation technique. Based on the results of data analysis, it was concluded that the motivation for memorizing the Qur'an at RA Darul Fikri Bringin Ponorogo was in the medium category. It is known from the results of the study which showed that the highest percentage was in the medium category as many as 15 respondents (41.6%). Meanwhile, children's memorization results at RA Darul Fikri Bringin Ponorogo are in the medium category. It is known from the results of the study which showed that the highest percentage was in the medium category as many as 16 respondents (44.4%). This means that there is a correlation between the motivation to memorize the Qur'an and the results of early childhood memorization at RA Darul Fikri Ponorogo.